(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The rapid transformation of education in the digital and knowledge-based society has highlighted the importance of creative thinking as a key competence of learners. Independent learning plays a crucial role in fostering creativity by promoting autonomy, self-regulation, and exploratory learning behaviors. This study investigates the mechanisms through which independent learning contributes to the development of creative thinking among students. The article analyzes theoretical foundations, identifies effective pedagogical mechanisms, and evaluates practical strategies that enhance creative cognitive processes. The findings indicate that self-directed tasks, reflective learning, problem-based activities, and digital learning environments significantly improve learners’ originality, flexibility, and critical thinking skills. The study concludes that integrating independent learning into educational practice is essential for preparing innovative and adaptive learners.